The Puritan Roots of American Universalism - Morris, K. R. (Scottish journal of theology, 1991)
If the Calvinism of America's Puritan forefathers is anything in relation to a belief in universal salvation, it is its opposite. The Calvinist's belief that Christ's atonement is restricted to effecting the salvation of a limited number of preordained saints is about as far as one can go in the opposite direction from universalism and still retain an aspect of grace and redemption for humanity. But in this essay I will argue that there was a direct link between the Puritan Calvinism of 17th century New England and the widespread movement toward universalism within New England churches in the late 18th and early 19th centuries.